Five Creeks, Clay County - Wood (Kansas State University, The Chapman Center for Rural Studies, 2011)
By definition, a township is a geographic division of six square miles that acts as a subdivision of a county. A township does not actually have to include a town to qualify as a township. Thus Five Creeks, located in Clay County, Kansas, is known to locals today, as it has been since its founding in 1871, as a town-less township
Wood, “Five Creeks, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/37.
Keywords: Bootleggers; Clay County; Five Creeks; Idana Presbyterian Church; Milford Dam Construction; W.A. Schoonover